Monitoring salivary immunoglobulin A responses to official and simulated matches In elite young soccer players - Freitas, C. G.; Aoki, M. S.; Arruda, A. F. S.; Franciscon, C.; Moreira, A. (Journal of Human Kinetics, 2016)
The purpose of the present study was to examine SIgA responses (concentration [SIgAabs] and a secretion rate [SIgArate]) to official and simulated competitive matches in young soccer players. The sample was composed of 26 male soccer players (age 15.6 ± 1.1 yrs, stature 177.0 ± 6.1 cm, body mass 70.5 ± 5.7 kg). Four soccer matches (two simulated matches [SM] and two official matches [OM]) were conducted. The matches consisted of two halves of 35 min with a 10 min rest interval. Each assessed player participated in only one SM and one OM. All matches were performed in the same week, during the competitive season, and at the same time of the day (9:00 am), separated by 48 h. Saliva samples were collected before and after every match. The session rating of perceived exertion was reported 30 min after each match in order to determine the internal training load (ITL). A significant decrease in SIgAabs and SIgArate after OM was observed when compared to the pre-match value. In addition, the SIgArate was higher at pre-OM when compared to pre-SM. A higher ITL for OM was observed compared to SM. The current findings indicate that OM may lead to a decrease in the main mucosal immunity function parameter of young soccer players that could increase the risk of URTI. Coaches should be aware of it in order to plan appropriate training loads and recovery procedures to avoid or minimize the likelihood of upper respiratory tract infection occurrences.